Climate-related financial policies as an enabler of circularity: a new insight from selected countries of the European Union - Nguyen Hong Yen; Le Thanh Ha (International Journal of Climate Change Strategies and Management)
Purpose – European economies must prioritize sustainable growth in their development goals by 2030. These countries’ aggressive economic progress necessitates considerable demands for energy and raw resources, posing environmental concerns like resource exploitation and garbage creation. Despite their recent great economic success, its environmental effect has been alarming. Circular economy strategies can increase resource efficiency by collecting and reusing trash in manufacturing processes, reducing waste creation. However, adopting a circular economy strategy also needs careful thought while deciding on pollution control technology in one sector to avoid the transmission of emissions and environmental concerns to business sectors. This study aims to examine the link between financial policies relating to climate change and circularity performance. Design/methodology/approach – The authors use a panel-corrected standard errors (PCSE) model, a feasible generalized least square model and the two-step general method of moment to explore this link. Furthermore, the results from the dynamic fixed effects in the autoregressive distributed lag method (DFE-ARDL) suggest the short-term and long-term relationships. Findings – The findings illustrate the heterogeneous influences of climate-related financial policies on the different issues of circularity performance. Furthermore, the results from the DFE-ARDL suggest that the impact of financial development only becomes apparent in the long term. The findings suggest that it is crucial to monitor the effects of financial policies on the transition toward the circular economy to develop better strategies and policies. Practical implications – The findings provide essential policy suggestions to help European countries design financial policies to pursue circular economies. Transitioning to a circular economy will undoubtedly present challenges and difficulties, with trade protectionism being one of the potential obstacles. European countries’ governments and authorities should actively encourage and enhance their capabilities to capitalize on opportunities created by the implementation of these climate-related financial policies. Among all approaches and tools to support nations in achieving the goal, the authors strongly recommend prioritizing the improvements of climate-related financial policy performance. The findings in the European region also suggest an insightful lesson for selecting an appropriate tool to facilitate other countries’ transition toward sustainable development and contributing to a greener world. Originality/value – This study examines the link between financial policies relating to climate change and circularity performance. In this paper, the authors contribute to the research in three ways. First, to the best of the authors’ knowledge, it is the first empirical study to explore climate-related financial policies as a contributor to the implementation of circularity. This research contributes to the existing body of information by investigating the climate-related financial policies’ influence on circularity performance as assessed by various dimensions. Various measures are used to gauge four dimensions of circularity performance in this paper. Economists and policymakers can use this index to develop and implement environmental policies by capturing multidimensional circularity performance issues. Second, this paper uses a PCSE model based on cross-sectional dependence and stationarity tests. The study focuses on countries in a European Union region, which contribute significantly to global carbon emissions and represent a varied spectrum of rich and emerging economies.